2014
DOI: 10.1002/jgrd.50863
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in Sahara desert sand emissivity during the dry season from IASI observations

Abstract: The problem of diurnal variation in surface emissivity over the Sahara Desert during non-raining days is studied and assessed with observations from the Infrared Atmospheric Sounding Interferometer (IASI). The analysis has been performed over a Sahara Desert dune target area during July 2010. Spinning Enhanced Visible and Infrared Imager observations from the European geostationary platform Meteosat-9 (Meteorological Satellite 9) have been also used to characterize the target area. Although the amplitude of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 42 publications
(64 reference statements)
2
40
0
Order By: Relevance
“…Meanwhile, as introduced by Li et al [64], an uncertainty of 1% in the emissivity in the reference channel (12 μm) can result in an error of about 0.5 K in LST. Recent research also showed the diurnal variation in surface emissivity during non-raining days [52,65,66]. Therefore, the simple setting of soil and vegetation emissivity in the study also will bring inevitable errors in soil and vegetation temperature estimation.…”
Section: Validation and Discussionmentioning
confidence: 97%
“…Meanwhile, as introduced by Li et al [64], an uncertainty of 1% in the emissivity in the reference channel (12 μm) can result in an error of about 0.5 K in LST. Recent research also showed the diurnal variation in surface emissivity during non-raining days [52,65,66]. Therefore, the simple setting of soil and vegetation emissivity in the study also will bring inevitable errors in soil and vegetation temperature estimation.…”
Section: Validation and Discussionmentioning
confidence: 97%
“…The transform has been successfully used with emissivity retrieval for IASI Masiello et al, 2014) and SEVIRI (Masiello et al, 2013b).…”
Section: Methodology: Implementation Of the Kalman Filter For (T S )mentioning
confidence: 99%
“…The remapping involves a high-spectral-resolution algorithm which is first applied to the 10-hinge-point UW/BFEMIS emissivities to generate the emissivity spectrum, which, in turn, is convolved with he SEVIRI spectral response. Details of this procedure can be found in Masiello et al (2013bMasiello et al ( , 2014. In passing, we note that the algorithm to transform UW/BFEMIS emissivities to high spectral resolution was first proposed and developed by Borbas and Ruston (2010).…”
Section: Ancillary Data: Emissivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Further details about the UW/BFEMIS emissivity transformation into the SEVIRI channel emissivity are reported in Masiello et al (2014); Serio et al (2013Serio et al ( , 2014.…”
Section: Datamentioning
confidence: 99%